Racism and Alienation in J M Coetzee’s novel Disgrace - Dr Shobha Tiwari Ray (Innovative Research Thoughts, 2023)
J.M. Coetzee's work Disgrace addresses the issues of racism and alienation via the tale of David Lurie, a white South African professor who is sacked from his position after having an affair with a student. As he flees to the farm of his daughter, Lucy, in the countryside, he is faced with the reality of life in post-apartheid South Africa. Racism is a recurrent issue throughout the work, as David Lurie's privileged status as a white man is juxtaposed with the realities of the black South Africans around him. Through his contacts with the farm workers and his daughter's neighbours, David starts to discover the degree to which racism is still pervasive in South Africa, even after the end of apartheid. He also grapples with his own role in this system since his romance with a black student is a representation of his entitlement and his assumption that he is beyond the laws that govern society. Alienation is another significant subject in the work, as David Lurie grows progressively separated from the people around him. His involvement with the student has left him without friends or coworkers, and his migration to the countryside only helps to further remove him from the world he previously knew. As he strives to adjust to his new surroundings and comprehend the individuals he meets, he becomes more conscious of his own feeling of dislocation. Ultimately, Disgrace is a stunning investigation of the legacy of racism in South Africa and the ways in which it continues to impact the lives of its residents. Through David Lurie's experiences, the storey emphasises the continual battle for peace and understanding in a society that remains bitterly divided.